« Un baromètre vivant ». Sur une métaphore proustienne - Swoboda, Tomasz (Studia Romanica Posnaniensia, 2021)
The article offers a study of two Proustian metaphors: “a living barometer” and “the little barometric figure”. After a brief reminder of the role of time in The Search for Lost Time, we move on to an analysis, sometimes intratextual, sometimes psychoanalytic, of the two metaphors, which places it in the context of family relationships and illness. Indeed, the barometric figure triggers a whole series of imaginary mechanisms which refer to the sensitivity and the constitutive versatility of the Search on the one hand, and to the writing itself on the other hand, but above all root this image in a complex game of identity tensions.